Respuesta :
The complete question is:
The recursive rule for a geometric sequence is given. [tex] a_{1}=2 [/tex]; [tex] a_{n}= 13*a_{n-1} [/tex]. Enter the explicit rule for the sequence.
Solution:
We are given
[tex] a_{1}=2 \\ \\ a_{n} = a_{n-1} [/tex]
Explicit rule of geometric sequence is of the form:
[tex] a_{n} = a_{1} (r)^{n-1} [/tex]
Using the given recursive sequence, we can find r.
[tex] a_{1}=2 [/tex]
[tex] a_{2}=13* a_{1}=13*2=26 [/tex]
r = Ratio of consecutive two terms of Geometric series.
So,
r = 26/2 = 13
Therefore,
[tex] a_{n}=2(13)^{n-1} [/tex] is the explicit rule for the given geometric sequence.
The recursive rule for a geometric sequence is given. [tex] a_{1}=2 [/tex]; [tex] a_{n}= 13*a_{n-1} [/tex]. Enter the explicit rule for the sequence.
Solution:
We are given
[tex] a_{1}=2 \\ \\ a_{n} = a_{n-1} [/tex]
Explicit rule of geometric sequence is of the form:
[tex] a_{n} = a_{1} (r)^{n-1} [/tex]
Using the given recursive sequence, we can find r.
[tex] a_{1}=2 [/tex]
[tex] a_{2}=13* a_{1}=13*2=26 [/tex]
r = Ratio of consecutive two terms of Geometric series.
So,
r = 26/2 = 13
Therefore,
[tex] a_{n}=2(13)^{n-1} [/tex] is the explicit rule for the given geometric sequence.
Answer:
The answer would actually be: [tex]2(\frac{1}{3})^{n-1}[/tex]
Step-by-step explanation:
I just took the test.